Immunological Correlates of the HIV-1 Replication-Competent Reservoir Size. (28th June 2021) - Ismail, Sherazaan D; Riou, Catherine; Joseph, Sarah B; Archin, Nancie M; Margolis, David M; Perelson, Alan S; Cassidy, Tyler; Abrahams, Melissa-Rose; Moeser, Matthew; Council, Olivia D; McKinnon, Lyle R; Osman, Farzana; et al.
Abstract: Understanding what shapes the latent human immunodeficiency virus type 1 (HIV-1) reservoir is critical for developing strategies for cure. We measured frequency of persistent HIV-1 infection after 5 years of suppressive antiretroviral therapy initiated during chronic infection. Pretreatment CD8 + T-cell activation, nadir CD4 count, and CD4:CD8 ratio predicted reservoir size.